Loss of Bicc1 impairs tubulomorphogenesis of cultured IMCD cells by disrupting E-cadherin-based cell-cell adhesion - Fu, Yulong (2010)
Bicaudal-C (Bic-C) gene was originally discovered in Drosophila melanogaster. The gene product Bic-C is thought to serve as an RNA-binding molecule targeting diverse proteins at the post-transcriptional level. Recent research has shown this gene to be conserved in many species, from Caenorhabditis elegans to humans. Disruption of this protein can disturb the normal migration direction of the anterior follicle cell of Drosophila oocytes, while mutation of a mouse Bicc1 (a mouse homologue of Bic-C) results in phenotypes mimicking human hereditary polycystic kidney disease (PKD). However, the cellular function of Bicc1 gene products in mammalian system remains largely unknown. In this study, we established stable IMCD (mouse inner medullary collecting duct) cell lines, in which Bicc1 was silenced by short hairpin RNA inhibition (shRNA). We show that inhibition of Bicc1 disrupted normal tubulomorphogenesis and induced cystogenesis of IMCD cells grown in three dimensional cultures. To determine what factors contributed to the defect, we systematically examined biological changes of Bicc1-silenced IMCD cells. We found that the cells had significant defects in E-cadherin-based cell-cell adhesion, along with abnormalities in actin cytoskeleton organization, cell-extracellular matrix interactions, cell proliferation, and apoptosis. These findings suggest that lack of Bicc1 leads to disruption of normal cell-cell junctions, which in turn impedes establishment of epithelial polarity. These cellular defects may initiate abnormal tubulomorphogenesis and cystogenesis of IMCD cells grown in vitro. The observation of aberrant cellular behaviors in Bicc1-silenced IMCD cells reveal functions for Bicc1 in renal epithelial cells and provides insight into a potential pathogenic mechanism of polycystic kidney disease.